Abortion language, nesting dolls theory, and an autoethnographic plea for radical transformation. Issue 4 (2nd October 2022) - Tillman, Stephanie; Johnson, Amber
ABSTRACT: Because of anti-abortion rhetoric, people must dedicate a lifetime to learning what decisions are one's own and how to talk about abortion socially, religiously, politically, secretly, and publicly. In this short article, we rely on the nesting doll theory to unpack the complex layers of rhetoric that control how people understand decision making processes regarding a body's reproductive potential. We use autoethnographic techniques to offer lived experience as evidence of the intricate ways anti-abortion rhetoric and reproductive in justice taints the entire system of bodily autonomy via guilt, shame, coercion, lack of consent, and, ultimately, lack of bodily autonomy.